Teachers’ Values as Predictors of Classroom Management Styles: A Relative Weight Analysis - Barni, Daniela; Russo, Claudia; Danioni, Francesca (Frontiers in Psychology, 2018)
Teachers potentially are important agents of socialization for their students and teachers’ values drive their goals and desirable behaviors. Teachers’ goals and behaviors are also primary influences on students’ achievement motivation and learning. This study – which referred to Schwartz’s Universal Theory of Human Values and involved 157 Italian high school teachers – focused on the relation between teachers’ personal values (i.e., the values teachers feel to be important for themselves) and socialization values (i.e., the values they would like their students to endorse) on the one hand, and their classroom management styles (authoritarian, authoritative, and permissive styles) on the other. Results showed the importance of values in determining the teaching styles, greater in the case of authoritative and authoritarian styles than of permissive style. Implications of these results for teachers’ practices and further expansions of the study are discussed.